Character Education Through the Example of The Prophet Muhammad SAW in The Book Nur al-Yakin Fi Sirah Sayyid al-Mursalin - Lasiman,; Roqib, Moh.; Nurfuadi,; Kirin, Arwansyah (Advances in Humanities and Contemporary Studies, 2024)
Education is an important pillar in forming individuals as a nation and the decline of civilization is the responsibility of the world of education. Character education has a higher position than moral education. Moral development is the first goal of attention in Islam. This can be seen from one of the apostolic missions of the Prophet Muhammad SAW, the main thing is noble morals. The Prophet Muhammad SAW was the last of Allah's Messengers, and he was sent to perfect the religion brought by the previous Prophets. Meanwhile, the aim of this research is to determine the exemplary character education of the Prophet Muhammad SAW in the book Nur Al-Yaqin Fi Sirah Sayyid Al-Mursalin by Sheikh Muhammad Al-Khudlari Bek. This type of research is library research, the data sources used in this research are obtained from primary data and secondary data. The data collection methods used were books, magazines, pamphlets, and other documentary materials. Data analysis in research uses a deductive thinking pattern, meaning research that starts from general statements and draws specific conclusions. The results of this research are: The exemplary character education of the Prophet Muhammad SAW in the book Nur Al-Yaqin Fi Sirah Sayyid Al-Mursalin by Sheikh Muhammad Al-Khudlari Bek contains character values, namely: religious, honest and trustworthy, patient, independent, brave, forgiving, fair, democratic and leader